In the Shadow of Death : Archibald Campbell Tait, Archbishop of Canterbury. - Witheridge, John (James Clarke Company, Limited, 2021)
In this, the first biography of Archibald Campbell Tait since his son-in-law, Randall Davidsons in 1891, John Witheridge tells the story of how a Scottish outsider became Queen Victorias favourite Archbishop of Canterbury, and the most powerful since Laud in the seventeenth century.
Description based upon print version of record.
Keywords: Tait, Archibald Campbell, -- 1811-1882.; Church of England -- Bishops -- Biography.; Church of England -- Évêques -- Biographies.; Tait, Archibald Campbell, -- 1811-1882; Church of England; Bishops -- Scotland -- Biography.; Évêques -- Écosse -- Biographies.; Bishops; Scotland; Christian Sects; Religion; Biographies